2019
DOI: 10.3389/fphar.2019.01346
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-Derived Paracrine Signals: Relevance for Neurogenic Niche Regulation and Blood–Brain Barrier Integrity

Abstract: Astrocytes are essential for proper regulation of the central nervous system (CNS). Importantly, these cells are highly secretory in nature. Indeed they can release hundreds of molecules which play pivotal physiological roles in nervous tissues and whose abnormal regulation has been associated with several CNS disorders. In agreement with these findings, recent studies have provided exciting insights into the key contribution of astrocyte-derived signals in the pleiotropic functions of these cells in brain hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 110 publications
(126 reference statements)
0
51
0
Order By: Relevance
“…Proper function of blood-and cerebral fluid-brain barriers are supervised by astrocytes. Astrocytes regulate BBB function in part by secretion of factors that modulate barrier properties in context-dependent fashion (66). The structural components of astrocytic endfeet also mediate interactions with the BBB.…”
Section: Astrocytes Display Wide Array Of Homeostatic Functionsmentioning
confidence: 99%
“…Proper function of blood-and cerebral fluid-brain barriers are supervised by astrocytes. Astrocytes regulate BBB function in part by secretion of factors that modulate barrier properties in context-dependent fashion (66). The structural components of astrocytic endfeet also mediate interactions with the BBB.…”
Section: Astrocytes Display Wide Array Of Homeostatic Functionsmentioning
confidence: 99%
“…In the mammalian CNS, neuron and glia interactions are complex. Astrocytes that are structurally related to the cortex glia in Drosophila, enwrap multiple neurons and NSCs, and are known to modulate adult neurogenesis through soluble signals such as morphogens and extracellular matrix proteins (reviewed by Spampinato et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of another type of glial cell, the astrocyte, at the NVU including BBB regulation has long been known (reviewed in [28]). Recently, Bonsack et al [29] demonstrated the importance of astrocyte-derived pentraxin-3 in regulating BBB permeability.…”
Section: Crosstalk and Cellular Signaling Within The Nvumentioning
confidence: 99%